Localism, Locavorism, and Animal Rights in Olga Tokarczuk’s Novel Drive Your Plow Over the Bones of the Dead - Petković, Danijela; Ljubinković, Dušica (Journal of Ecohumanism, 2022)
Relying on insights from CAS (Critical Animal Studies), especially Vasile Stanescu’s and Robert C. Jones’s recent work on locavorism, and the studies of localism (by Andrew Stables, David Hess, Timothy O’Riordan and Doreen Massey, inter alia), the paper presents a reading of Olga Tokarczuk’s 2009 novel Drive Your Plow Over the Bones of the Dead which highlights the conflict between localism and locavorism on the one side, and universal animal rights on the other. Localism, often greeted as a form of resistance to globalization for its assertion of the distinctiveness of place and the reaffirmation of boundaries (O’Riordan), and locavorism, a neologism which suggests that eating locally, animals included, is the only road to environmental sustainability, are treated in Tokarczuk’s novel as mere ideological justification for the violence against animals, the natural world, and the less privileged members of the human community, at the hands of traditionalist local authorities.